Child soldiers in Colombia: Five views (2012)
This paper offers explanations of the meanings that push children to illegally armed groups in Colombia from the testimony of 21 demobilized young girls from the region of Antioquia (Colombia). The girls’ answers are placed on a typology of explanations drawn from academic reports, and compared to three samples of attributions of students, teachers and policemen of their same region. The visions “idealizing” and “criminalizing” mobilization are practically marginal in all samples. The dominant vision among the girls is called “self-assertive”. From the rest of the samples, as well as for the experts, the majority of the views are “victimizing”.